Antibacterial Activity of Biodegradable Films Incorporated with Biologically-Synthesized Silver Nanoparticles and the Evaluation of Their Migration to Chicken Meat - Meiriele da S. das Neves; Sara Scandorieiro; Giovana N. Pereira; Jhonatan M. Ribeiro; Amedea B. Seabra; Adriana P. Dias; Fabio Yamashita; Claudia B. dos R. Martinez; Renata K. T. Kobayashi; Gerson Nakazato (Antibiotics, 2023)
The food industry has been exploring the association of polymers with nanoparticles in packaging production, and active products are essential to increase the shelf life of food and avoid contamination. Our study developed starch-poly (adipate co-terephthalate butyl) films with silver nanoparticles produced with Fusarium oxysporum components (bio-AgNPs), intending to control foodborne pathogens. The bio-AgNPs showed activity against different Salmonella serotypes, including multidrug-resistant Salmonella Saint Paul and Salmonella Enteritidis, with minimum bactericidal concentrations ranging from 4.24 to 16.98 µg/mL. Biodegradable films with bio-AgNPs inhibited the growth of up to 106Salmonella isolates. Silver migration from the films to chicken was analyzed using electrothermal atomic absorption spectrophotometry, and the results showed migration values (12.94 mg/kg and 3.79 mg/kg) above the limits allowed by the European Food Safety Authority (EFSA) (0.05 mg/kg). Thus, it is necessary to improve the technique to avoid the migration of silver to chicken meat, since these concentrations can be harmful.